Pengaruh Disiplin Kerja dan Lingkungan Kerja Fisik terhadap Kinerja Pegawai pada Kantor Desa Selapajang Kecamatan Cisoka Kabupaten Tangerang - Rismala, Indria Nova Sekar; Syarifah Ida Farida (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study to determine the effect of Work Discipline on Employee Performance, to determine the effect of Physical Work Environment on Employee Performance and to determine Work Discipline and Physical Work Environment on Employee Performance at the Selapajang Village Office, Cisoka District, Tangerang Regency. The research methodology uses quantitative methods. The sample used in this study was 85 respondents. The analysis method used is a partial test (t test) and a simultaneous test (f test). The results of the study indicate that: 1) Work Discipline has a positive and significant effect on Employee Performance at the Selapajang Village Office, Cisoka District, Tangerang Regency, as evidenced by the t-count value of 8.462> t-table 1.989 with a significance of 0.000 <0.05. 2) Physical Work Environment has a positive and significant effect on Employee Performance at the Selapajang Village Office, Cisoka District, Tangerang Regency, as evidenced by the t-count value of 10.930> t-table 1.989 with a significance of 0.000 <0.05. 3) Work Discipline and Physical Work Environment have a positive and significant effect on Employee Performance at the Selapajang Village Office, Cisoka District, Tangerang Regency, as evidenced by the calculated f value of 67.589 > ftable 3.11 with a significance of 0.000 < 0.05.